Estructura diamétrica y stock de carbono en las especies comerciales de un bosque de colina baja de la comunidad nativa Nuevo Remanente, Loreto, 2022 - Canaquiri Pizango, Santos Celestino (2023)
Diametric structure and carbon stocks in commercially significant species were measured in a low hill forest in the district of El Tigre, Loreto, Peru. Forest census data from cutting plot (CP) 1 operational plan (OP) 1 were evaluated for commercial species. The species with the most trees in the area are Virola albidiflora, Otoba parvifolia, Albizia subdimidiata, Macrolobium acaciifolium and Cedrelinga cateniformis. The diameter classes of 50 cm to 60 cm (2.40 trees/ha), 60 cm to 70 cm (1.87 trees/ha) and 70 cm to 80 cm (2.99 trees/ha) show the highest values. The carbon stock is 36.86 tC/ha, or 30 284.46 tC. The highest concentrations of carbon stocks are found in the species Cedrelinga cateniformis (5.44 tC/ha), Virola albidiflora (3.08 tC/ha), Albizia subdimidiata (2.81 tC/ha), Otoba parvifolia (2.27 tC/ha) and Macrolobium acaciifolium (2.21 tC/ha). The diameter classes of 60 to 70 cm (8.45 tC/ha), 70 to 80 cm (7.50 tC/ha) and 110 cm and more (6.61 tC/ha) show the highest concentrations of carbon stocks. The statistical analysis indicates that there is either no association or a weak relationship between diameter structure, biomass and carbon stocks (r=0.024 in both cases; significance level = 0.01 in both cases).